2019
DOI: 10.3390/min9100645
|View full text |Cite
|
Sign up to set email alerts
|

Injection of a CO2-Reactive Solution for Wellbore Annulus Leakage Remediation

Abstract: Driven by concerns for safe storage of CO2, substantial effort has been directed on wellbore integrity simulations over the last decade. Since large scale demonstrations of CO2 storage are planned for the near-future, numerical tools predicting wellbore integrity at field scale are essential to capture the processes of potential leakage and assist in designing leakage mitigation measures. Following this need, we developed a field-scale wellbore model incorporating (1) a de-bonded interface between cement and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A longer residence time of calcite water led to larger amounts of in situ precipitated minerals, which also promoted self-healing in CO 2 storage wells. Wolterbeek and Wasch and Koenen investigated microannular damage and found that injecting water containing Ca 2+ ions into fractures within the damaged cement sheath could lead to calcite water reacting with CO 2 in the fractures, resulting in the formation of solidified calcium carbonate. This effectively sealed the fractures and demonstrated the self-healing capability of CO 2 storage wells.…”
Section: Key Factors Influencing Co2 Geological Storagementioning
confidence: 99%
“…A longer residence time of calcite water led to larger amounts of in situ precipitated minerals, which also promoted self-healing in CO 2 storage wells. Wolterbeek and Wasch and Koenen investigated microannular damage and found that injecting water containing Ca 2+ ions into fractures within the damaged cement sheath could lead to calcite water reacting with CO 2 in the fractures, resulting in the formation of solidified calcium carbonate. This effectively sealed the fractures and demonstrated the self-healing capability of CO 2 storage wells.…”
Section: Key Factors Influencing Co2 Geological Storagementioning
confidence: 99%
“…Under flow conditions, it was found these reactions can lead to effective self-sealing of micro-annuli, provided that the precipitation of carbonates locally outstrips dissolution of cement phases. This prompted several workers to speculate whether CO 2 -rich fluids could be employed in wellbore seepage remediation [49,50]. Conversely, however, if dissolution dominates, then reactive transport could conceivably lead to extensive cement degradation and self-enhanced seepage, with sealing integrity worsening over time [65].…”
Section: Sodium Bicarbonatementioning
confidence: 99%
“…More and more studies have shown that CO 2 possibly migrates to shallow aquifers and pollutes freshwater resources (Carroll et al, 2014; Keating et al, 2013; Ruggieri & Gherardi, 2020; Smith et al, 2013; Takaya et al, 2017; Wang & Wang, 2018). This CO 2 leakage to freshwater layers may cause groundwater acidification (Apps et al, 2010), heavy metal mobilization (Frye et al, 2012), or mineral dissolution (Fazeli et al, 2019; Wang et al, 2023; Wang & Jaffe, 2004; Wasch & Koenen, 2019). Therefore, a comprehensive risk assessment of caprock integrity or caprock sealing efficiency is an essential task for CO 2 geosequestration safety.…”
Section: Introductionmentioning
confidence: 99%